Engagement of circular RNA HECW2 in the nonautophagic role of ATG5 implicated in the endothelial-mesenchymal transition. Issue 3 (4th March 2018) - Yang, Li; Han, Bing; Zhang, Yuan; Bai, Ying; Chao, Jie; Hu, Gang; Yao, Honghong
ABSTRACT: Endothelial-mesenchymal transition (EndoMT) is associated with damage to blood-brain barrier (BBB) integrity. Circular RNAs (circRNAs) are highly expressed in the brain and are involved in brain diseases; however, whether circRNAs regulate the EndoMT in the brain remains unknown. Our study demonstrated that circHECW2 regulated the EndoMT by directly binding to MIR30D, a significantly downregulated miRNA from miRNA profiling, which subsequently caused an increased expression of ATG5. These findings shed new light on the understanding of the noncanonical role of ATG5 in the EndoMT induced by methamphetamine (Meth) or lipopolysaccharide (LPS). The in vivo relevance was confirmed as microinjection of circHecw2 siRNA lentivirus into the mouse hippocampus suppressed the EndoMT induced by LPS. These findings provide novel insights regarding the contribution of circHECW2 to the nonautophagic role of ATG5 in the EndoMT process in the context of drug abuse and the broad range of neuroinflammatory disorders.